Regional Free Trade Agreement as the form of ‘New Regionalism’ in Asia Pacific: Geo-Politic and Geo-Economic Aspect of ASEAN Centrality - Purbantina, Adiasri Putri (Global and Policy Journal of International Relations, 2015)
ABSTRACTWhile most of the theories of regionalism give more focus on the study of regional institutions (neo-liberal institutionalism approach), or on the identity aspect of regionalism (constructivist approach), regionalism can also be analyzed under the international political economy (IPE) framework. Kevin G Chai in his book, The Politics of Economic Regionalism, uses (IPE) theory to analyses the regional economic integration in East Asia. The increasing number of regional FTAs as the new form of regionalism is basically driven by strategic interest, such as economy and politics. This paper seeks to explain the ‘new regionalism’ in Asia Pacific (the noodle bowl of FTAs), by understanding the geo-political and geo-economic aspects of Association of Southeast Asian Nations (ASEAN). There are two main arguments here: 1) under the ‘new regionalism’, the driving force of this regional FTAs is not regional identity but geo-politic and geo-economic value of particular region; 2) The ASEAN Economic Community (AEC) can be viewed as the form of dependency to the geo-economy and geo-politics interests of the major economy powers in Asia Pacific region.The main section for this paper is divided into four parts. The first one is the history of new regionalism and the IPE theoretical approach. The second one is the dynamics of economic regionalism process in Asia Pacific region. The third one is the geo-political and geo-economic aspects of ASEAN for Asia Pacific Regionalism frameworks.Keywords: New Regionalism, Economic Regionalism, Geo-political, Geo-economyDOI:https://doi.org/10.33005/jgp.v3i02.1937